2015
DOI: 10.3390/biomedicines3030248
|View full text |Cite
|
Sign up to set email alerts
|

Aptamers and Their Significant Role in Cancer Therapy and Diagnosis

Abstract: Aptamers are nucleic acid/peptide molecules that can be generated by a sophisticated, well-established technique known as Systematic Evolution of Ligands by EXponential enrichment (SELEX). Aptamers can interact with their targets through structural recognition, as in antibodies, though with higher specificity. With this added advantage, they can be made useful for clinical applications such as targeted therapy and diagnosis. In this review, we have discussed the steps involved in SELEX process and modification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 118 publications
0
18
0
Order By: Relevance
“…The main challenge in the development of reliable diagnostic sensors based on antibodies is due to the fluctuation of their affinity depending on manufacture and batch. Synthetic aptamers overcome these limitations as their properties at the same conditions depend only on nucleotide sequence [ 105 , 106 ]. Another advantage of using aptamers over the conventional antibodies is the possibility to modify them chemically with various labels, active groups, and nanoparticles, which is important for biosensors design [ 105 ].…”
Section: Lung Cancer Diagnosis Using Aptamersmentioning
confidence: 99%
See 1 more Smart Citation
“…The main challenge in the development of reliable diagnostic sensors based on antibodies is due to the fluctuation of their affinity depending on manufacture and batch. Synthetic aptamers overcome these limitations as their properties at the same conditions depend only on nucleotide sequence [ 105 , 106 ]. Another advantage of using aptamers over the conventional antibodies is the possibility to modify them chemically with various labels, active groups, and nanoparticles, which is important for biosensors design [ 105 ].…”
Section: Lung Cancer Diagnosis Using Aptamersmentioning
confidence: 99%
“…Synthetic aptamers overcome these limitations as their properties at the same conditions depend only on nucleotide sequence [ 105 , 106 ]. Another advantage of using aptamers over the conventional antibodies is the possibility to modify them chemically with various labels, active groups, and nanoparticles, which is important for biosensors design [ 105 ]. Some aptamers change their conformation after binding to their target molecules, which makes the development of switchable aptasensors and fluorescence quenching sensors possible, which could not be achieved with antibodies [ 107 ].…”
Section: Lung Cancer Diagnosis Using Aptamersmentioning
confidence: 99%
“…The incubator (Sanyo MCO-17AI, LabX, Tokyo, Japan) was set at 37 °C with a carbon dioxide concentration equal to 5%. The passage of confluent control cells were performed with trypsinizing the cells using 0.25% w/v trypsin plus 0.53 mM ethylenediaminetetraacetic acid (EDTA) solution [ 9 ]. The passage of confluent target cells was different from control cells.…”
Section: Methodsmentioning
confidence: 99%
“…To date, many papers have reported the advantages of sensors for the diagnosis of prostate, breast and colon cancers [ 9 , 10 , 11 , 12 ]. Among the few papers detailing the use of apta-DSs for colon cancer diagnosis, Sheng et al reported a microfluidic device incorporated with a large number of micro-pillars used for isolating HCT 116 cancer cells from a blood sample [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aptamers are short, single-chained DNA or RNA molecules that recognize molecular targets with high affinity (in nM to pM range) and specificity owing to their 3D conformation. Aptamers are emerging as a class of biocompatible ligands with huge potential in diagnostics and therapeutics [ 15 , 16 , 17 ]. Compared with antibodies, aptamer production exploits a chemical technology with high batch fidelity that is not intrinsically prone to viral or bacterial contamination [ 15 ].…”
Section: Introductionmentioning
confidence: 99%